Quantificação de escleródios e germinação miceliogênica e carpogênica de Sclerotinia sclerotiorum oriundos da cultura da soja tratada química e biologicamente - Crato, Fausto Fernandes do (2013)
Sclerotinia stem rot caused by Sclerotinia sclerotiorum is spreading every year in soybean fields. Due to the survival capacity in soil using specialized structures, called sclerotia, and environmental conditions favorable for germination, the use of Integrated Disease Management is essential. Better understanding of pathogen biology is obtained by quantifying the pathogen in the soil and, subsequently, determining its viability through carpogenic and myceliogenic sclerotia germination. This study quantified the number and surface area of sclerotia using the Quant Program and determined the effect of different chemical and biological treatments on germination (carpogenic and myceliogenic) of S. sclerotiorum. Treatments consisted of biological and chemical products sprayed in soybean crop while the culture was growing; sclerotia were obtained after soybean threshing, separating them from the grains. Quantification of sclerotia number and surface area were obtained using the Quant program, from UFV. In order to determine if sclerotium specific size affects its germination, sclerotica were separated in three different size fractions. Sclerotia viability was determined by inducing myceliogenic and carpogenic germination. Myceliogenic germination was conducted in PDA medium with incubation in a growth chamber at 25 °C with 12 hours lighting. Germination evaluation was done after 24, 48, 72, and 96 hours incubation. Carpogenic germination was done in sterilized soil and incubation in a growth chamber at 20 ± 2ºC, 12 hours lighting and soil moisture at field capacity. The experimental design was completely randomized, in split plots, where the plot factors were 3 treatments and the split plots were the 3 fractions sizes, with 4 repetitions. The results showed that the Quant program was efficient in quantifying the number and area of sclerotia, while the chemical treatments were more effective in reducing the number of sclerotia than the biological ones. Chemical treatment was most effective in sclerotia myceliogenic germination inhibition, while the biological treatments inhibited sclerotia carpogenic germination more effectively. Smaller sclerotia had greater carpogenic germination viability than the bigger ones.